2017
DOI: 10.14299/ijser.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Modulates Prohibitin and Cytoskeleton in the Retinal Pigment Epithelium

Abstract: The retinal pigment epithelium (RPE) plays imperative roles in normal retinal function by photoreceptor protection from light and phagocytosis of rod and cone outer segments during disc shedding. Melatonin is the free radical scavenger and circadian determinant to protect the RPE and retina from oxidative stress and regulate the circadian clock. The current study tested the hypothesis whether melatonin could affect cytoskeletal structure within RPE. Our Western blot analysis demonstrated that melatonin treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Rho belongs to the Ras superfamily of low molecular weight GTPases, which have a key role in the formation of the alveolar epithelial cell cytoskeleton, as well as Rho-associated coiled-coil forming protein kinase (110). Sripathi et al (111) reported that MT treatment could be beneficial in protecting mitochondria under oxidative stress and maintaining the structure of the cytoskeleton in the retinal pigment epithelium. Moreover, p120 serves as an essential protein in the regulation of cell junctions and protects against VILI by regulating both adherens and tight junctions by reducing the degradation of occludin via the inhibition of RhoA activity (112).…”
Section: Mt and Vilimentioning
confidence: 99%
“…Rho belongs to the Ras superfamily of low molecular weight GTPases, which have a key role in the formation of the alveolar epithelial cell cytoskeleton, as well as Rho-associated coiled-coil forming protein kinase (110). Sripathi et al (111) reported that MT treatment could be beneficial in protecting mitochondria under oxidative stress and maintaining the structure of the cytoskeleton in the retinal pigment epithelium. Moreover, p120 serves as an essential protein in the regulation of cell junctions and protects against VILI by regulating both adherens and tight junctions by reducing the degradation of occludin via the inhibition of RhoA activity (112).…”
Section: Mt and Vilimentioning
confidence: 99%
“…We have investigated the therapeutic applications of retinal degeneration by focusing on antiapoptotic and neuroprotective mechanisms using a functional proteomics approach. Previously, we demonstrated that the retinal expression of erythropoietin (EPO), the visual cycle, and the subsequent kinase phosphorylations are interconnected to the circadian clock in anticipation of daily light onset . Our data demonstrated that the EPO is a neuroprotective molecule involved in the inhibition of the apoptotic pathway, including BCL-xL and caspase-9.…”
Section: Introductionmentioning
confidence: 89%
“…Cells were grown on sterile glass cover slips using DMEM/F12 medium with 10% FBS and 1% penicillin/streptomycin (Hyclone) in 5% CO 2 incubator at 37°C. Cells were treated under oxidative stress or intense light as previously reported [9][10][11][18][19][20]. Cells were washed with PBS and incubated with MitoTracker Orange CMTMRos (100 nM, Molecular Probes, Carlsbad, CA) in serum-free culture medium (30 min, 37°C), followed by washing (PBS) and fixing (10% formaldehyde, 30 min, room temperature).…”
Section: Immunocytochemical Analysismentioning
confidence: 99%